2012
DOI: 10.1039/c2lc00030j
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic-based device for study of transendothelial invasion of tumor aggregates in realtime

Abstract: Circulating tumor aggregates exhibit a high metastatic potential and could potentially serve as an important target for cancer therapies. In this study, we developed a microfluidic model that reconstitutes and is representative of the principal components of biological blood vessels, including vessel cavity, endothelium, and perivascular matrix containing chemokines. Using this model, the transendothelial invasion of tumor aggregates can be observed and recorded in realtime. In this study we analyzed the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 42 publications
6
128
0
3
Order By: Relevance
“…cancer cell migration, adhesion (23), and extravasation (24,25). Recently, our group presented a microfluidic model to investigate the specificity of breast cancer metastasis to bone, providing quantitative data on cancer cell extravasation rate and reproducing the effects of the CXCL5-CXCR2 interaction between bone cells and metastatic breast cancer cells observed in vivo (26).…”
Section: Significancementioning
confidence: 99%
“…cancer cell migration, adhesion (23), and extravasation (24,25). Recently, our group presented a microfluidic model to investigate the specificity of breast cancer metastasis to bone, providing quantitative data on cancer cell extravasation rate and reproducing the effects of the CXCL5-CXCR2 interaction between bone cells and metastatic breast cancer cells observed in vivo (26).…”
Section: Significancementioning
confidence: 99%
“…Zhang et al [119] demonstrated that chemokine CXCL12 could stimulate salivary gland adenoid cystic carcinoma cells to extravasate through HUVEC endothelium. The stimulated extravasation can also be inhibited by CXCR4 antagonist AMD3100.…”
Section: Metastatic Niche: Modelling Tumour -Stroma Interaction and Mmentioning
confidence: 99%
“…Common methods to create capillary lumen structures as microvasculatures include moulding the capillaries in hydrogels by needles or rods [95][96][97][98], by photoresists [99][100][101], by sacrificial carbohydrates [102] or creating lumens based on viscous fingering instabilities [103,104]. Alternatively, an endothelial vascular network as the microvasculature can be formed by endothelial sprouting in hydrogels [105][106][107][108][109][110][111][112], monolayer on ECM hydrogel [113][114][115] or on a porous membrane [116,117], and monolayer in microchannels [118,119] (figure 2l ).…”
Section: Microfluidic Tumour -Microvascular Modelmentioning
confidence: 99%
“…Then the fMLP gradient was applied for cell migration experiment. Similar microfluidics-based strategy for transendothelial migration has been reported previously [60][61][62] . Our preliminary results consistently show that neutrophils can migrate into the 10 nM fMLP source channel through the barrier channel and an additional HUVEC layer (Fig.…”
Section: Memory Effect Of Neutrophil Chemotaxismentioning
confidence: 83%